2011
DOI: 10.1021/jp206967b
|View full text |Cite
|
Sign up to set email alerts
|

Glutamic Acid Adsorption and Transformations on Silica

Abstract: We report here on the adsorption and deposition of L-glutamic acid (Glu) on an amorphous silica and its subsequent thermal transformations. When adsorbed from aqueous solutions, Glu only has a low affinity for the silica surface but at high concentrations the adsorbed molecules serve as nuclei for the formation of small glutamic acid crystallites. As long as the Glu loading remains inferior to a saturation limit (about 0.5 molecule nm À2 ), the thermal behavior of adsorbed Glu is significantly different from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 43 publications
(74 citation statements)
references
References 78 publications
6
67
0
1
Order By: Relevance
“…This pH-dependent adsorption has been also observed by other authors via acid-base titration experiments. Bouchoucha et al 211 and Gao et al 253 also observed low amounts of Glu adsorption on amorphous silica and SBA-15, respectively, which was attributed to the negligible difference in pH between the pI of Glu and the PZC of these silica materials (around 3).…”
Section: General Trends Found In the Amino Acid Adsorption On Silica mentioning
confidence: 95%
See 4 more Smart Citations
“…This pH-dependent adsorption has been also observed by other authors via acid-base titration experiments. Bouchoucha et al 211 and Gao et al 253 also observed low amounts of Glu adsorption on amorphous silica and SBA-15, respectively, which was attributed to the negligible difference in pH between the pI of Glu and the PZC of these silica materials (around 3).…”
Section: General Trends Found In the Amino Acid Adsorption On Silica mentioning
confidence: 95%
“…For instance, bulk amino acid crystals were evidenced both in Gly/SiO 2 210 and Glu/SiO 2 . 211 An interesting phenomenon that will be discussed in Section 9.1.1.2 is that in the case of Gly, excess glycine precipitated as the metastable  polymorph, while the  form is normally observed upon precipitation from a clean solution.…”
Section: X-ray Diffractionmentioning
confidence: 99%
See 3 more Smart Citations